Digital Integrated Marketing Communications Strategies in Building Local Cultural Image for Achieving Tourism Sustainability: The Role of Local Community Involvement - Lintang Cahya Rahmat Kinasih; Muhammad Sufyan Abdurrahman (Jurnal Indonesia Sosial Teknologi, 2024)
This study explores the impact of Digital Integrated Marketing Communications (DIMC) strategies and local cultural image promotion on tourism sustainability, with a focus on local community involvement as a moderating factor. The primary objective is to understand how effective digital marketing and cultural promotion contribute to sustainable tourism practices and how community engagement enhances these effects. A quantitative research design was employed, utilizing Structural Equation Modeling (SEM) for data analysis. Data were collected from 200 respondents, including tourists and stakeholders at cultural tourism destinations, using a structured questionnaire with a 1-5 Likert scale to measure DIMC strategies, cultural image promotion, tourism sustainability, and community involvement. The study finds that both DIMC strategies and the promotion of local cultural image positively impact tourism sustainability. Furthermore, local community involvement significantly moderates these relationships, enhancing the effectiveness of marketing and cultural promotion efforts in supporting sustainable tourism. This research contributes to the theoretical understanding of the interplay between digital marketing, cultural promotion, and sustainability by highlighting the crucial role of community involvement. Practically, it underscores the need for tourism managers to integrate local perspectives into their marketing strategies and cultural promotion efforts to achieve more sustainable outcomes. The study provides valuable insights for enhancing the effectiveness of tourism marketing and promoting cultural heritage while supporting sustainable tourism development.